Gratitude and Its Relationship to Resilience and Academic Performance among University Students - Nailah Najwa, Zainoodin; Ida Juliana, Hutasuhut; Mohamad Azhari, Abu Bakar; Nurul, Wardhani (UNIMAS Publisher, 2021)
This study examines the relationship between gratitude, resilience, and academic performance among students of a public university in Malaysia. One hundred and forty-six samples were obtained through a simple random technique (N=235). The survey employed GQ6 (Gratitude Questionnaire), Brief Resilience Scale (BRS), and self-reported grade-point average (GPA) as its measurement tools. Correlation analysis shows that gratitude has a high positive relationship with resilience and academic performance. Findings from the study support those of previous studies about the importance of gratitude in improving student’s psychological resilience and academic performances. The study suggests that adopting a sense of gratefulness and appreciation helps students overcome challenges in their educational journey at university.